Exploring the Influence of Habits and Facilitating Conditions on Qris Usage Intention Among Generation Z in Denpasar (International Journal of Economics and Management Research, 2026)
Abstract: This study explores the interrelationships among attitude, trust, and behavioral intention, particularly within the context of technology adoption and digital payments. Attitude, defined as an individual's evaluation of objects or behaviors, plays a crucial role in shaping behavioral intentions. Recent literature highlights that positive attitudes toward technology significantly enhance the likelihood of adoption. Trust, another vital component, influences user engagement and decision-making processes in digital environments. It is posited that trust in technology providers enhances user willingness to adopt new platforms, thereby impacting their behavioral intentions. This paper synthesizes findings from various studies conducted between 2020 and 2025, emphasizing the importance of understanding these constructs in fostering effective technology adoption strategies. Ultimately, the integration of attitude, trust, and behavioral intention provides valuable insights for researchers and practitioners aiming to improve user engagement and satisfaction in digital transactions.